(untitled) (ETNOSIA : Jurnal Etnografi Indonesia, 2020)
This article aims to review the book with the title of Black Mecca: The African Muslims of Harlem by Zain Abdullah. Abdullah’s (2010) Mec Black Mecca ’adds to the growing body of literature on Islam influenced by the post-modernists’ challenges to neo-Orientalist Western representations of Islam (Al Azmeh 1993: 140). They are called for a historicized and contextualized view of Islam and Muslims, steering away from essentializing identity politics. Abdullah’s (2010) thick ethnography, or as he describes it, "narrative style," presents a variety of anecdotes and experiences along gendered, class, and generational lines, with a common Muslim orientation towards environment and experiences.